Predicting metabolic fluxes from omics data via machine learning - Gonçalves, Daniel M. (2023)
The authors also wish to acknowledge the European Union's Horizon BioLaMer project under grant agreement number [ 101099487 ]. Publisher Copyright: © 2023 The Authors